Analysis of the Implementation of Stunting Handling Policy Programs - Devi Kurniati; Rukmaini Rukmaini; Retno Widowati (Indonesian Journal of Global Health Research, 2026)
The prevalence of stunting in Bogor City in 2024 will be 18.2%. The national target is 14%. Policy analysis is needed to identify the success and obstacles of stunting management policy programs in the community. To conduct an analysis of the implementation and effectiveness of stunting handling policy programs in Bogor City based on stakeholder information. Qualitative descriptive research with in-depth interviews and observations of 16 informants consisting of (Head of Health Office, Head of Health Center, Coordinating Midwife, Posyandu Cadres, and Toddler Women) in Tanah Sareal and South Bogor Districts, Bogor City. Evaluation criteria based on William N. Dunn. Data were analyzed using NVivo 15 through thematic analysis. Data analysis produced 5 major themes, namely (program management and leadership, labor and cost barriers, social problems and citizens' habits, changes in officers' habits and responses, suggestions and expectations for the future), 12 categories and 65 codes. The policy runs effectively through the commitment of regional leaders (cross-sector coordination) and digital innovation of virtual referrals (Important Mess). The efficiency aspect is hampered by double input, limited nutritional personnel, and time-lag problems of logistics data. Socioculturally, parental denial and traditional parenting are challenges. However, the responsiveness of officers through the action of "picking up the ball" (sweeping) has proven to be successful in transforming people's behavior in fulfilling animal protein and toddlers' rest patterns. The stunting handling program in Bogor City has high responsiveness but is constrained by the efficiency of the workload of health workers and sociocultural barriers to the family. The Anuh Larang, Penting Lur, and Taleus Bogor programs increase the coverage of services, changes in family behavior, and community nutrition awareness. However, implementation still faces limitations in human resources, administrative burden, and regional capacity disparities.